Comparison of RCI001 and corticosteroid on the effects on intraocular pressure in mice - Kim, Soo Hyun; Ku, Young-ah; Yoo, Chungkwon; Kim, Yong Ho; Kim, Dong Hyun (Frontiers in medicine, 2023)
RCI001, a novel therapeutic candidate for the treatment of ocular inflammatory diseases, have demonstrated remarkable anti-inflammatory and antioxidant effects in various ocular experimental models. This study was to evaluate the effects of RCI001 on intraocular pressure (IOP) and compare them with those of corticosteroids in experimental mouse models.PurposeRCI001, a novel therapeutic candidate for the treatment of ocular inflammatory diseases, have demonstrated remarkable anti-inflammatory and antioxidant effects in various ocular experimental models. This study was to evaluate the effects of RCI001 on intraocular pressure (IOP) and compare them with those of corticosteroids in experimental mouse models.Experimental mice were randomly divided into naïve, phosphate-buffered saline (PBS), 0.1% dexamethasone (DEX-1), and 1% RCI001 (RCI) groups, and each reagent was pipetted into the right eye of the mouse at 10 μL thrice daily for 5 weeks. In addition, 20 μL of 0.1% dexamethasone was injected subconjunctivally into the right eye once weekly for 5 weeks in the DEX-2 group. The IOP was measured under anesthesia at baseline and twice weekly for 5 weeks. The △IOP (%) was defined as the change in IOP from baseline [△IOP (%) = (IOPweek5-IOPbaseline)/IOPbaseline × 100%]. The anterior segments were clinically and histologically examined.MethodsExperimental mice were randomly divided into naïve, phosphate-buffered saline (PBS), 0.1% dexamethasone (DEX-1), and 1% RCI001 (RCI) groups, and each reagent was pipetted into the right eye of the mouse at 10 μL thrice daily for 5 weeks. In addition, 20 μL of 0.1% dexamethasone was injected subconjunctivally into the right eye once weekly for 5 weeks in the DEX-2 group. The IOP was measured under anesthesia at baseline and twice weekly for 5 weeks. The △IOP (%) was defined as the change in IOP from baseline [△IOP (%) = (IOPweek5-IOPbaseline)/IOPbaseline × 100%]. The anterior segments were clinically and histologically examined.There was no significant increase in IOP and △IOP (%) [values by week 3 (day 21) in any of the groups]. However, IOP and △IOP (%) in the DEX-2 group tended to increase slightly after day 10 compared with baseline. Compared with baseline IOP values, the DEX-1 group showed a statistically significant increase in IOP at weeks 4 and 5, and the DEX-2 group at week 5. The △IOP (%) of the DEX-1 and DEX-2 groups (%) at week 5 were 38.2% ± 5.8% and 38.4 ± 4.6%, respectively. However, the IOP in the RCI group did not increase significantly until week 5. The RCI group did not show notable corneal changes, such as epithelial defects or stromal opacities, at week 5. In addition, hematoxylin and eosin (H&E) staining of corneas in the RCI group revealed healthy corneal epithelial, stromal, and endothelial integrity.ResultsThere was no significant increase in IOP and △IOP (%) [values by week 3 (day 21) in any of the groups]. However, IOP and △IOP (%) in the DEX-2 group tended to increase slightly after day 10 compared with baseline. Compared with baseline IOP values, the DEX-1 group showed a statistically significant increase in IOP at weeks 4 and 5, and the DEX-2 group at week 5. The △IOP (%) of the DEX-1 and DEX-2 groups (%) at week 5 were 38.2% ± 5.8% and 38.4 ± 4.6%, respectively. However, the IOP in the RCI group did not increase significantly until week 5. The RCI group did not show notable corneal changes, such as epithelial defects or stromal opacities, at week 5. In addition, hematoxylin and eosin (H&E) staining of corneas in the RCI group revealed healthy corneal epithelial, stromal, and endothelial integrity.Long-term use of RCI001 did not induce significant IOP elevation or ocular surface changes, whereas topical corticosteroids significantly increased the IOP. Therefore, RCI001 may be an effective anti-inflammatory agent with a low risk of drug-induced IOP elevation.ConclusionLong-term use of RCI001 did not induce significant IOP elevation or ocular surface changes, whereas topical corticosteroids significantly increased the IOP. Therefore, RCI001 may be an effective anti-inflammatory agent with a low risk of drug-induced IOP elevation.